Probiotics supplementation for the obesity management; A systematic review of animal studies and clinical trials. (January 2019) - Ejtahed, Hanieh-Sadat; Angoorani, Pooneh; Soroush, Ahmad-Reza; Atlasi, Rasha; Hasani-Ranjbar, Shirin; Mortazavian, Amir M.; Larijani, Bagher
Graphical abstract: Highlights: Probiotic supplementation may help managing obesity via modulating gut microbiota. This systematic review revealed that probiotic supplementation can have beneficial effects on body weight parameters. The anti-obesity effect of probiotic supplements is species- and strain-specific. Abstract: Obesity has been declared as global epidemic that has nearly doubled during recent decades. In this systematic review, PubMed, Web of Science, EMBASE, Cochrane and Scopus databases were searched for entire animal studies and clinical trials focusing on the effects of various probiotic supplements on obesity up to September 2018. Of 3405 studies identified through searching literatures, finally 72 experimental studies and 15 clinical trials were included. Among the animal studies, probiotic supplementation led to reduced weight gain or fat accumulation in 61 studies using different strains of Lactobacillus and Bifidobacterium . Five of clinical trials were conducted on obese children and adolescents. Three of them revealed positive results, one of them showed no effect and the other one caused weight gain. Among the other ten clinical trials conducted on obese adults, nine studies showed probiotic efficiency in reducing weight or waist circumferences. Specific strains of probiotics had anti-obesity effects.